The Effect of Work Competence, Work Motivation, and Work Discipline On Work Performance - R. Reynilda (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to analyze and investigate the relationship between Work Competence, Work Motivation, Work Discipline, and Work Performance in Cooperatives and SMEs Office employees of South Sulawesi Province. The population of this study was all civil servants (PNS) related to the SME sector of the Cooperatives and SMEs Office of South Sulawesi Province, with a total sample of 45 respondents. We collected data using a questionnaire and data processing using multiple linear regression analysis. The study's results stated that all independent variables had a positive and significant effect on the dependent variable.